Endotoxin‐induced cerebral pathophysiology: differences between fetus and newborn. Issue 4 (20th February 2019) - Feng, Susan Y. S.; Hollis, Jacob H.; Samarasinghe, Thilini; Phillips, David J.; Rao, Shripada; Yu, Victor Y. H.; Walker, Adrian M.
Abstract: As the comparative pathophysiology of perinatal infection in the fetus and newborn is uncertain, this study contrasted the cerebral effects of endotoxemia in conscious fetal sheep and newborn lambs. Responses to intravenous bacterial endotoxin (lipopolysaccharide, LPS) or normal saline were studied on three consecutive days in fetal sheep (LPS 1  μ g/kg, n  = 5; normal saline n  = 5) and newborn lambs (LPS 2  μ g/kg, n  = 10; normal saline n  = 5). Cerebro‐vascular function was assessed by monitoring cerebral blood flow (CBF) and cerebral vascular resistance (CVR) over 12 h each day, and inflammatory responses were assessed by plasma TNF alpha (TNF‐ α ), nitrate and nitrite concentrations. Brain injury was quantified by counting both resting and active macrophages in the caudate nucleus and periventricular white matter (PVWM). An acute cerebral vasoconstriction (within 1 h of LPS injection) occurred in both the fetus (ΔCVR +53%) and newborn (ΔCVR +63%); subsequently prolonged cerebral vasodilatation occurred in the fetus (ΔCVR −33%) in association with double plasma nitrate/nitrite concentrations, but not in the newborn. Abundant infiltration of activated macrophages was observed in both CN and PVWM at each age, with the extent being 2–3 times greater in the fetus ( P  < 0.001). In conclusion, while the fetus and newborn experience a similar acute disruption of the cerebral circulation after LPS, the fetus suffers a more prolonged circulatory disruption, a greater infiltration of activated macrophages, and an exaggerated susceptibility to brain injury. Abstract : Though the fetus and newborn experience a similar acute disruption of the cerebral circulation in endotoxaemia, the fetus suffers a more prolonged circulatory disruption, a higher plasma nitric oxide production, a greater infiltration of activated macrophages, and an exaggerated susceptibility to brain injury. The differences will shed light on further research and target interventions in perinatal infection.